PERAN GURU DALAM PENGELOLAAN KELAS UNTUK MENINGKATKAN KEAKTIFAN BELAJAR SISWA KELAS IV SDN MERAPI 1 - Syahmi Honsa Labibah; Meyla Fazza Putri Azzahra; Suherli Kusmana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning activeness can be understood as students' efforts to develop their potential through a series of learning activities to achieve learning objectives. In practice, field conditions are not yet fully ideal: most students remain passive, tend to be silent when given questions, and in group activities only a small portion actually discuss to complete tasks. If left unaddressed, this condition risks reducing learning quality and student learning outcomes. This study aims to describe the role of the Grade IV teacher at SDN Merapi 1 in managing the classroom to encourage student learning activeness. The study uses a descriptive qualitative approach with interview techniques conducted with the homeroom teacher and two students. Results show that the teacher performs differentiated learning planning based on student ability mapping, arranges the learning environment and agrees on class rules with students, implements varied learning strategies including educational games, and maintains active communication with parents. A positive teacher-student relationship, family support, and an individual approach have proven to be key factors in encouraging student participation, while the main obstacle faced is the low involvement of some parents in accompanying the child's learning process at home.